Pemilihan Jenis Batuan Oleh Masyarakat Prasejarah Di Kawasan Impak Meteorit Bukit Bunuh, Lenggong, Perak Dan Sumbangannya Kepada Teknologi Paleolitik - Rashidi, Nur Asikin (2013)
Bukit Bunuh is one of the Palaeolithic sites in meteorite impact area, located in Lenggong Valley which is 10 kilometers away from the city of Lenggong in the Hulu Perak district. This study was conducted to determine the raw materials and technology used by Palaeolithic societies in Bukit Bunuh thereby to testify the impact of meteorite in the area. Impact of a meteorite on Bukit Bunuh has been proved based on the world meteorite impact criteria listed in the table of The Planetary and Space Science Centre (PASSC), University of Brunswick, Canada. The table list of the six criteria such (i) macrostructure shatter cone, (ii) impact microstructure -PDF, (iii) coesite and stishovite minerals, (iv) impact crater, (v)impact melt, and (vi) suevite and including two more evidences such as specific gravity and existed of remnant meteorite (metals). Proof of a meteorite impact in Bukit Bunuh was based on the comparative studies, mapping, field analysis and scientific studies in the laboratory such as petrographic studies, XRF, XRD, SEM, stereomicroscope and specific gravity. Comparison of raw materials was carried on Southeast Asian Palaeolithic sited as well as their relationships with meteorite impact sites of the world.